SUPPLEMENTATION: PREVALENCE AMONG PRACTITIONERS OF BODYBUILDING (Fiep Bulletin - online, 2014)
The search for better peformance has become more common among bodybuilders , that to achieve best results make the use of dietary supplements , little is known about practitioners' knowledge about dietary supplements . This study aimed to evaluate the knowledge of some bodybuilders gyms . The population was defined by body builders for a total sample of 100 practitioners of both genders , who answered a questionnaire with 16 questions concerning the profile of research . It was found that 88 % ( n = 88) evaluated received some information about supplementation however erroneously as the main sources were the internet 23 % ( n = 52 ) , friends 18% ( n = 40 ) and teacher academy with 17 % ( n = 38 ) . The supplements most often cited by creatine were evaluated with 15 % ( n = 71 ) , bcaa 13 % ( n = 61 ) , albumin 11 % ( n = 51 ) and 10 % whey protein ( n = 45 ) , the data show that practitioners use the products at certain times of the training period 72 % ( n = 63 ) and that consumption is done before 43 % ( n = 62 ) and then 29 % ( n = 42 ) training. The main reason to use is the possible improvement in training 37 % ( n = 50 ) and the main goal is the search for muscle hypertrophy 23 % ( n = 43 ) . The professional who has authorization to prescribe and indicate that nutritional supplementation is the research appears in 10 % ( n = 13 ) Quote indicating the products, the most cited is the physical education teacher of 30 % ( n = 37 ) of this an awareness is required of practitioners and professionals in physical education, which are audits of sales of these products , guidance on the subject supplementation should be done emphasizing the importance of appropriate professional when making use of dietary supplements.
Keywords: Food Supplements; Bodybuilding; Nutrition .